2018
DOI: 10.4025/actascianimsci.v41i1.42557
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot performance and carcass yield of Hararghe Highland (<i>Bos indicus</i>) bulls using different concentrate feeds

Abstract: A study was conducted to evaluate the feedlot performance and carcass yield of Hararghe Highland bull using different types of concentrate feeds fed grass hay as a basal diet in eastern Ethiopia. Thirty Hararghe Highland bulls were blocked by weight and randomly allocated to one of the following six treatments. T1 = Hay ad libitum + 4kg dried cafeteria leftover; T2 = Hay ad libitum + 4kg wheat bran; T3 = Hay ad libitum + 4 kg d-1 maize grain; T4 = Hay ad libitum + 4kg d-1 mix (1:1, wheat bran to maize grain, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
2
2
Order By: Relevance
“…The observed lower final weight, weight gain, and average daily gain of about 248.2 kg, 55.7 kg, and 0.79 kg shown on bulls fed on D3 compared to other dietary treatments were associated with the low nutritive value of D3 due to the inclusion low-nutrient feeds in the diet. The value of the full gastro-intestinal tract of 27.1 kg obtained from this study was higher than that obtained by Gebremariam et al [24] The highest values of the full gastro-intestinal tract shown in D1 were associated with the palatability of the diet, since D1 contained molasses and maize bran, which both have high palatability, leading bulls fed on D1 to have higher intake than in D2 and D3.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The observed lower final weight, weight gain, and average daily gain of about 248.2 kg, 55.7 kg, and 0.79 kg shown on bulls fed on D3 compared to other dietary treatments were associated with the low nutritive value of D3 due to the inclusion low-nutrient feeds in the diet. The value of the full gastro-intestinal tract of 27.1 kg obtained from this study was higher than that obtained by Gebremariam et al [24] The highest values of the full gastro-intestinal tract shown in D1 were associated with the palatability of the diet, since D1 contained molasses and maize bran, which both have high palatability, leading bulls fed on D1 to have higher intake than in D2 and D3.…”
Section: Discussioncontrasting
confidence: 79%
“…These difference could be associated with the efficiency of utilization of the energy and protein in the formulated diets as similarly noted by Moloney et al [27]. The mean value of dressing percentage obtained from the present study was slightly higher than that obtained from other studies [24] which could again attributed due to higher energy and protein intake by the bulls, which increases carcass weight and hence dressing percentage [28]. From the strain difference, the highest values of HLL (99.8 cm), CD (55.6 cm) HLL (65.0 cm) and HLC (98.7cm) were shown on Boran bulls, followed by Iringa red, and the lowest values were shown on Singida white bulls.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the overall dressing percentage value in the current study was higher than previous works on similar breeds by [12] and [16] those previous report by [12] and [26]. Dressing percentage variation may occur as a result of differences on the genotypes, localities and/or conditions of animals [27], sex and age of the animals [11].…”
Section: Carcass and Non-carcass Characteristicscontrasting
confidence: 72%
“…However, little information is available so far on yields, meat cut and quality characteristics of indigenous cattle breeds in Ethiopia [9] [10]. Some studies were conducted in different corners of the country at different experimental stations like: on Harar bulls [11], Borana, Arsi, and Harar bulls [12], Boran, Kereyu and Ogaden [13] [14] cattle carcass characteristics. However, little information is available on carcass characteristics, meat yield, yield percentage and meat cut of Ethiopian cattle finished under similar preslaughter management.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia's low production potential, according to Alemu et al [4], may be caused by the genetic limitations of indigenous breeds of livestock and management techniques like feeding systems and health care services. Many studies [7] [8] [9] [10] [11] confirm the significant impacts of breed, age at which animal slaughter, and feeding levels. The carcass weight of Hararghe highland cattle per head varies in ranges of 46.4 to 86.80 kg, 115.1 to 165.4 kg, and 106.2 to 115.6 kg [7] [9] [10], which is less than the world and East Africa averages carcass weight, 212 kg and 143 kg [12], respectively.…”
Section: Introductionmentioning
confidence: 99%